Redactable consortium blockchain based on verifiable distributed chameleon hash functions - Wu, Xiangyu; Du, Xuehui; Yang, Qiantao; Wang, Na; Wang, Wenjuan (Journal of parallel and distributed computing, 2024)
With the evolving application demands, the inherent immutability of consortium blockchains hinders their widespread adoption. For example, expired data stored on the chain cannot be deleted, and erroneous data cannot be redacted, seriously limiting the flexibility of consortium blockchains. However, existing redactable blockchain solutions need to be improved in aspects of decentralization, efficiency, and fault tolerance. This paper develops a new verifiable distributed chameleon hash (VDCH) function to solve the above problems. With VDCH, nodes share chameleon keys with a secure multi-party computation protocol based on a verifiable key-sharing scheme, and the collision shares can be verified with a Schnorr non-interactive zero-knowledge proof protocol, which enhances the fault tolerance of the consortium chain while maintaining its decentralized nature. Then, this paper proposes a consensus protocol called CVTSS based on verifiable threshold signatures, which provides protocol support for collaborative hash collision computation by multiple nodes using VDCH, thus avoiding the dependence on Nakamoto consensus and improving the redaction efficiency. Meanwhile, CVTSS uses threshold signatures to prevent malicious nodes from tampering with data using one-time chameleon keys. Finally, this paper constructs an efficient, practical, and secure redactable consortium chain scheme based on VDCH and CVTSS. Theoretical analysis and experimental results show that the proposed scheme can operate safely in the presence of malicious nodes with an acceptable time cost. •This paper proposes a verifiable distributed chameleon hash function - VDCH.•VDCH makes the process of computing hash collisions fault-tolerant.•This paper proposes a threshold signature-based consensus protocol - CVTSS.•The feasibility and security of our scheme are proven by both theoretical analysis and experimental evaluations.•Experiments show that our scheme is fault-tolerant and highly efficient.